The Effect of Alkaloids Extract of Amaranthus gracilis (L.) on Some Biological Aspects of House Fly Musca domestica(L.) - H. Alkafaji, Asmaa; S. Alzubaidi, Fawzi (Iraqi Journal of Science, 2026)
Present study is carried out to evaluate the effect of alkaloids extract ofAmaranthus gracilis on some biological aspects of the house fly Musca domestica tofind out the best way for their control. The highest mortality percentage on eggs ofthe house fly was 83.3% at concentration of 10 mg/ml followed by 44.4% and31.1% at 7.5 mg/ml and 5 mg/ml respectively. Results also referred that themortality rates of eggs, larvae, pupae were increased with increasing concentration.The pupal weights were decreased with increasing of concentration.